An Analysis of Grammatical Errors in Students’ Writing of Economic Students at Universitas Pandanaran Semarang - Tiara Nove Ria; Maria Magdalena Minarsih (Universitas Pandanaran, 2021)
This study aimed to find out the grammatical errors made by the students in essay writing. English as a foreign language that the students learn on campus is needed to improve their skills to face their future. Therefore, writing is one of the English skills that they must master. However, writing is not easy for them to learn because they have to master grammar as one variable in writing. Therefore, a lecturer has to know the weakness, especially in the students’ grammar, so that s/he can know how to teach the students. The subject of this study were 32 students of Economic Faculty in the first semester at Universitas Pandanaran. The method of this study was descriptive qualitative. The result was concluded that the most errors did by the students are spelling and punctuation with the percentage 42.4%, then followed by word order with the error rate of 15.4%. The third error with a percentage of 13.3% is the use of the article. Then 11.2% errors of sentence pattern, preposition with error rate 5.6%, plurality 4%, verb tense and form 3.3%, pronoun 2.8%, and the last is the subject-verb agreement with the rate of error is 2%.Keywords: analysis, grammatical error, writing